Temperature Dependence of Oxygen Release from LiNi0.6Mn0.2Co0.2O2 (NMC622) Cathode Materials for Li-Ion Batteries. Issue 11 (7th September 2018) - Jung, Roland; Strobl, Philipp; Maglia, Filippo; Stinner, Christoph; Gasteiger, Hubert A.
Abstract : Promising cathode materials for Li-ion batteries are layered transition metal oxides (LiNix Mny Coz O2, NMC). Here, we will investigate the temperature dependence of oxygen release from NMC622, caused by the transformation of the near-surface structure from the layered to spinel and/or rock-salt structure. We will demonstrate that oxygen release is not a potential driven process but occurs once ∼81% of the lithium ions are removed from the NMC structure. Consequently, the onset potential for oxygen release in NMC-graphite cells decreases only by ∼60 mV from 4.42 V at 25°C to 4.36 V at 50°C, which is simply due to lower overpotentials at higher temperature. The amount of evolved oxygen increases significantly with increasing temperature, indicating the formation of thicker spinel/rock-salt surface layers. As the released oxygen causes chemical oxidation of the electrolyte, the amounts of CO2 and CO occurring simultaneously with O2 release also increase with temperature. Further experiments in NMC-Li cells as well as with 13 C-labelled ethylene carbonate (EC) electrolyte show that CO2 evolved prior to O2 release results from i) EC hydrolysis and ii) electrolyte impurity oxidation. In agreement with the onset potentials for oxygen release, we will show that stable cycling of NMC622-graphite full-cells is possible at the different temperatures up to ∼81% state-of-charge.